(untitled) (The Pakistan Development Review, 2011)
The main task of the macroeconomic policy-makers is to control unemployment and inflation at the minimum possible level. Different policies have been tried to control inflation at its minimum possible level and inflation targeting is the most popular among them. It is the commitment to maintain inflation at the announced level and use interest rate as an instrument to control it if it is expected to diverge from the announced level. However in a higher denominated debt. country Central Bank is reluctant to increase interest rate because it pressurises the foreign exchange market, which leads to exchange rate depreciation. If there is exchange rate pass through effect to prices, depreciation leads to increase in prices. Thus increase in interest rate does not decrease prices instead results in increase in prices. The two important linkages were tested in this study are (i) increase in real interest rate depreciates the currency, and (ii) depreciation in real exchange rate leads to increase in prices. Using VAR model we concluded that real exchange rate is not significantly associated to the real interest rate in the short run and exchange rate pass through effect to prices is not present in Pakistan.